تقييم سمك الطبقة التالفة لنماذج خرسانية مسلحة معرضة للحريق: Evaluate the Depth of Destroyed Layer for Reinforcement Concrete Samples Exposed to Fire (Diyala Journal of Engineering Sciences, 2014)
952 ( ملم ونماذج مكعبات ×522× تقييم تاثير الحرق على سلوك نماذج سقوف خرسانية مسلحة بأبعاد ) 522 952 ( ملم وفق تصميم خلطة خرسانية بمقاومة انضغاط 42 ميكا باسكال. تم تعريضها إلى لهب ×952× بأبعاد ) 952 النار المباشر من السطح الأسفل لثلاثة مستويات من الح ا ررة ) 822،522،422 ( م° لمدة ساعة واحدة. بعد تبريد النماذج إلى درجة الح ا ررة الاعتيادية تم أج ا رء فحصين لا اتلافيين هما فحص الأمواج فوق الصوتية وفحص مطرقة شميدت المرتدة قبل وبعد الحرق. كما وتم تحديد عمق الطبقة التالفة لنماذج السقوف بعد الحرق.وقورنت النتائج مع نماذج المكعبات بعد تعرضها إلى نفس الظروف التي عرضت إليها نماذج السقوف الخرسانية المسلحة لغرض إيجاد التغيير في الوزن, مقاومة الانضغاط, سرعة الموجات و رقم الارتداد. واعتمادا على نتائج هذا البحث شهدت نتائج فحص الانضغاط انخفاضا بمقدار %22 ( في درجة ح ا ررة 422 مْ ،) 26 %( في درجة ح ا ررة 522 مْ ،) 46 %( في درجة ح ا ررة 822 مْ , وان مقدار الفقدان ( 9,1 9,5 (% على التوالي لمستويات درجات الح ا ررة أعلاه, وان - - - (،%)9,5 9,0(، %) بالوزن ظهر ) 2,55 2,5 62 60 (% على التوالي لمستويات - - - (،%)11 18(،%) الانخفاض في سرعة الموجات فوق الصوتية كان بمقدار ) 86 80 22 (% على التوالي لمستويات ( ,%)02( ,%) درجات الح ا ررة أعلاه, كذلك تبين انخفاض في رقم الارتداد وبمقدار ) 92 درجات الح ا ررة أعلاه.The behavior of reinforcement concrete slab dimension (500x500x150) mm and the cubes dimension (150 x 150 x 150 )mm samples are evaluated to the effect of fire according to the mix design concrete 40 Mpa compressive strength. The samples are exposited to the direct flame fire from down surface for three level of temperature degree (400,500 and 600) C° for one hour. After the samples are cooled to the normal degree of temperature, two non-distractive test are carried out: pulse velocity and shmidt hammer before and after the fire. Also the destroy layer depth is measured for the slab samples after the fire so the samples of cubes are prepared and tested after burning at the same circumstance which appear to slab reinforcement samples are purposed to found the change of the weight ,the compressive strength, pulse velocity and the number of rebound. The results indicate to (30%) reducing in compressive strength at level of temperature degree 400 C°, and  (38%) reducing in compressive strength at level of temperature degree 500 C°, (48%) reducing in compressive strength at level of temperature degree 600 C°. The weight loss appear (0.5-0.55) %, (1.2-1.5) %, and (1.5-1.7) % for three level of temperature degree (400, 500 and 600) C°. Also, the atrsonic pulse velocity is decreased (62-68) %, (76-79) %, and (82-83) % for three level of temperature degree (400,500 and 600) C°.